EFEKTIVITAS DESAIN MODEL PEMBELAJARAN ARIAS - Julrissani, Julrissani; Setiawan, Setiawan (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2023)
Students' lack of self-confidence in learning results in fear of generating an idea. So there is a need for learning models that can improve students' creative thinking abilities, one of which is the ARIAS learning model to awaken the abilities of active students. This research aims to determine the effectiveness of the ARIAS learning model on students' creative thinking abilities. This type of research is quantitative with an experimental approach. The population in this study was in class IV, totaling 40 people. Divided into 20 students in the experimental class and 20 students in the control class. Sampling in this research used random sampling. Data collection techniques used test techniques in this research in the form of pretest and posttest with analysis using SPSS 25. Hypothesis testing used Uji-t. Based on the research results obtained tcount = 2,882 > ttable = 1,686 at a significance level of 0.05, which means that Ho is rejected and Ha is accepted. It can be concluded that the ARIAS learning model is effective in strengthening students' creative thinking so as to produce improved learning outcomes than before.